ANALISIS KONSEPTUAL PERAN GURU DALAM MENGURANGI MISKONSEPSI SISWA TENTANG VOLUME DAN LUAS PERMUKAAN BANGUN RUANG DI SEKOLAH DASAR - Zahra Nur Zaskiya; Amelia Fakhira Siregar; Safira Safira; Silva Nuria Azahra; Hafiziani Eka Putri (Journal of Innovation Research and Knowledge, 2026)
Misconceptions in learning the concepts of volume and surface area of three-dimensional shapes remain a persistent issue among elementary school students. These misconceptions, such as the inability to distinguish between volume and surface area, errors in formula application, and misunderstanding of measurement units, hinder students’ conceptual understanding and problem-solving abilities. This study aims to analyze the teacher’s role in reducing students’ misconceptions through a systematic and conceptual approach. The research employed a Systematic Literature Review (SLR) method by analyzing 25 relevant scientific articles published between 2019 and 2025, sourced from Google Scholar and Sinta-indexed journals. The data were analyzed using the PRISMA framework, including identification, screening, eligibility, and review stages, followed by qualitative descriptive synthesis. The findings reveal that misconceptions are primarily caused by rote learning practices, lack of concrete learning media, and the mismatch between instructional methods and students’ cognitive development at the concrete operational stage. Furthermore, the study identifies four integrative teacher roles: as a learning designer implementing the Concrete-Pictorial-Abstract (CPA) approach, a facilitator providing contextual and hands-on experiences, a motivator fostering a supportive learning environment, and an evaluator utilizing diagnostic and formative assessments. These roles function cyclically to detect, prevent, and address misconceptions effectively. In conclusion, optimizing the teacher’s integrative role is crucial in minimizing misconceptions and enhancing meaningful mathematical understanding in elementary education.Keywords: misconceptions, teacher role, volume and surface area, elementary education, mathematics learning